Cooperativism as a strategy for territorial development in La Plata, Huila (Colombia) - Medina Bermúdez, Onias Arnulfo (Cooperativismo & Desarrollo, 2025)
This article analyzes the role of coffee cooperatives as a territorial development strategy in La Plata, Huila (Colombia), through a case study of Global Cafés. Based on the premise that rural cooperatives not only facilitate coffee marketing but also generate social, economic, and organizational transformations in their territories, it investigates how this organization has contributed to the resilience of small producers. Using a qualitative approach and the case study method, information was collected through semi-structured interviews with members of the cooperative. The results show that, in addition to offering stable prices and better sales conditions, Global Cafés provides revolving loans, advances for coffee orders, access to inputs, and a solidarity fund, thereby strengthening economic autonomy and social cohesion. Challenges such as the lack of its own headquarters, limitations in certifications, and low youth participation were also identified. It is concluded that cooperativism, when rooted in the local social fabric, acts as an agent of territorial transformation, promoting equity, sustainability, and endogenous development.